Cytomegalovirus shedding in seropositive healthy women of reproductive age in Tianjin, China. (2020) - Ju, D.; Li, X. Z.; Shi, Y. F.; Li, Y.; Guo, L. Q.; Zhang, Y.
Abstract: Cytomegalovirus (CMV) enters latency after primary infection and can reactivate periodically with virus excreted in body fluids which can be called shedding. CMV shedding during the early stage of pregnancy is associated with adverse pregnancy outcome. The shedding pattern in healthy seropositive women who plan to have babies has not been well characterised. Vaginal swabs, urine and blood were collected from 1262 CMV IgG-positive women who intended to have babies and tested for CMV DNA by fluorogenic quantitative PCR method. Serum IgM was also detected. The association between sociodemographic characteristics and CMV shedding prevalence was analysed. Among 1262 seropositive women, 12.8% (161/1262) were detected CMV DNA positive in at least one body fluid. CMV DNA was more frequently detected in vaginal secretion (10.5%) than in urine (3.2%) and blood (0.6%) also with higher viral loads ( P < 0.00). CMV shedding was more likely detected in IgM-positive women than IgM-negative women (29.5% (13/44) vs. 12.2% (148/1218); OR 3.03, 95% CI 1.55–5.93; P = 0.001). CMV shedding in vaginal secretion was highly correlated with shedding in urine, the immune state of IgM, the adverse pregnant history and younger age. CMV shedding was more commonly detected in vaginal secretion than in urine or blood with higher viral loads among healthy seropositive women of reproductive age. Further studies are needed to figure out whether the shedding is occasional or continuous and whether it is associated with adverse pregnancy outcomes.